The Concept of Safe Houses for Domestic Violence Victims in Aceh: A Maṣlaḥah Perspective - Muslem Abdullah; Muhammad Siddiq Armia; Husni Mubarrak (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2026)
The conventional criminal justice system often marginalizes the rights of domestic violence victims due to its predominantly offender-oriented approach. This article aims to reconstruct the concept and operational standards of safe houses (Rumah Aman) for domestic violence victims under the Integrated Service Unit for Women and Children Empowerment (UPTD PPA) in Aceh Province. Employing empirical legal research methods through field observations, this study analyzes the dialectic between Indonesian positive law and Islamic law through the lens of Mashlahah Theory. The main findings reveal that within the context of Aceh, the existence of safe houses transforms from a mere state administrative mandate into a theological obligation. Through the Mashlahah framework, safe houses serve as a frontline instrument to protect the five fundamental principles of Islamic law (al-mabadi' al-khams): religion, life, intellect, lineage, and wealth. The novelty of this study lies in its integration of the state's formal protection system with local cultural-theological legitimacy. This research concludes the necessity of a holistic reconceptualization of safe house standardization encompassing high-level physical security, psychological rehabilitation, and economic empowerment reinforced by religious authorities to ensure effective victim protection in a special autonomous region.